ANALISIS TEKNIK BERNYANYI DIANA DAMRAU PADA OPERA “THE MAGIC FLUTE ARIA QUEEN OF THE NIGHT” KARYA WOLFGANG AMADEUS MOZART - DEDI BENSAMAS LUMBAN GAOL (Universitas Negeri Medan, 2018)
This study aims to analyze, Technique of Singing Diana Damrau oin Opera TheMagic Flute Aria Queen Of The Night Works Wolfgang Amadeus Mozart. Thepurpose of this research is to know Technique of Singing, how to interpret andartistic overall Diana Damrau sing Opera The Magic Flute Aria Queen Of TheNight.The theory used is analyze, vocal technique, sound processing, sound formation,breathing, frasering, head voice, powering, vibrato, interpretation, singing, opera,aria,The method used in this research is qualitative descriptive method, namely aresearch method that aims to describe in detail and clearly about a phenomenonthat became the focus of research. This research is a qualitative descriptivelaboratory works, thus this research is held in the laboratory of sendratasik musiceducation program of state university of Negeri Medan. The results showed thatDiana Damrau sang aria by using singing technique that is base of vocaltechnique. The achievement of singing technique has been applied verry well,where the singging technique is articulation, breathing, posture, resonance,vibrato, intonation. This factor becomes the main point that from the analysis, ithas a verry high singing technique singing aria Queen Of The Night. DianaDamrau had application interpreation that is, the dynamics of mp, mf, f, ff, ff,aksen, sfz, fp, cressendo, descressendo. Tempo allegro assai, ad libitum,allargando.Style singging marcatto, alla marcia, legato, recitaive, ekspreso,stacatto, sustenuto, emozione. Angry authoritarian, direspectful and desire is anexpression Diana to sing the aria. On the basis of it can be started that the overallappearance of Diana Damrau is interconnected to build on the builder’s point tomake the appearance of Diana Damrau towards spectaculer.